Future challenges and chances in the diagnosis and management of invasive mould infections in cancer patients. (8th September 2020) - Vehreschild, Jörg Janne; Koehler, Philipp; Lamoth, Frédéric; Prattes, Juergen; Rieger, Christina; Rijnders, Bart J A; Teschner, Daniel
Abstract: Diagnosis, treatment, and management of invasive mould infections (IMI) are challenged by several risk factors, including local epidemiological characteristics, the emergence of fungal resistance and the innate resistance of emerging pathogens, the use of new immunosuppressants, as well as off-target effects of new oncological drugs. The presence of specific host genetic variants and the patient's immune system status may also influence the establishment of an IMI and the outcome of its therapy. Immunological components can thus be expected to play a pivotal role not only in the risk assessment and diagnosis, but also in the treatment of IMI. Cytokines could improve the reliability of an invasive aspergillosis diagnosis by serving as biomarkers as do serological and molecular assays, since they can be easily measured, and the turnaround time is short. The use of immunological markers in the assessment of treatment response could be helpful to reduce overtreatment in high risk patients and allow prompt escalation of antifungal treatment. Mould-active prophylaxis could be better targeted to individual host needs, leading to a targeted prophylaxis in patients with known immunological profiles associated with high susceptibility for IMI, in particular invasive aspergillosis. The alteration of cellular antifungal immune response through oncological drugs and immunosuppressants heavily influences the outcome and may be even more important than the choice of the antifungal treatment. There is a need for the development of new antifungal strategies, including individualized approaches for prevention and treatment of IMI that consider genetic traits of the patients. Lay Abstract: Anticancer and immunosuppressive drugs may alter the ability of the immune system to fight invasive mould infections and may be more important than the choice of the antifungal treatment. Individualized approaches for prevention and treatment of invasive mold infections are needed.